2000
DOI: 10.1021/jm990599h
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of (R)- and (S)-2- and 6-Fluoronorepinephrine and (R)- and (S)-2- and 6-Fluoroepinephrine:  Effect of Stereochemistry on Fluorine-Induced Adrenergic Selectivities

Abstract: Several routes to the enantiomers of fluoronorepinephrines (1) and fluoroepinephrines (2) were explored. A catalytic enantioselective oxazaborolidine reduction and a chiral (salen)Ti(IV) catalyzed asymmetric synthesis of silyl cyanohydrins proved efficacious in the key stereo-defining steps of two respective routes. Binding studies of the catecholamines with alpha(1)-, alpha(2)-, beta(1)-, and beta(2)-adrenergic receptors were examined. The assays confirmed that fluorine substitution had marked effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The highly selective ␣AR agonist 6-fluoronorepinephrine (6FNE), possesses an approximately 10-and 1000-fold selectivity for ␣ 1 ARs and ␣ 2 ARs, respectively, compared with ␤ARs (Lu et al, 2000). We first examined the effects of 6FNE on burst discharges to corroborate the type of ␣AR action on hippocampal activity observed in our previous studies (Jurgens et al, 2005).…”
Section: Hippocampal Ca3 Pyramidal Cell Characterizationmentioning
confidence: 92%
“…The highly selective ␣AR agonist 6-fluoronorepinephrine (6FNE), possesses an approximately 10-and 1000-fold selectivity for ␣ 1 ARs and ␣ 2 ARs, respectively, compared with ␤ARs (Lu et al, 2000). We first examined the effects of 6FNE on burst discharges to corroborate the type of ␣AR action on hippocampal activity observed in our previous studies (Jurgens et al, 2005).…”
Section: Hippocampal Ca3 Pyramidal Cell Characterizationmentioning
confidence: 92%
“…Method IV is based on a N-formylation of the primary amine (MDA) with ethyl formate (HCO 2 Et) providing the corresponding formamide intermediate (IVa) which after reduction with lithium aluminium hydride gave the N-methyl compound (MDMA) [34,35] in relative good yields.…”
Section: Chemistrymentioning
confidence: 99%
“…5 This methodology has been applied to the asymmetric synthesis of fluorinated norepinephrines and fluorinated epinephrines. 6 A closely related vanadium(salen) complex was also found to catalyse the asymmetric addition of trimethylsilyl cyanide to aldehydes. 7 We have shown that complex 1 (and the related vanadium(salen) complex) will catalyse the asymmetric addition of potassium cyanide to an aldehyde in the presence of an anhydride, thus providing an asymmetric synthesis of cyanohydrin esters (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%